First evidence of Blastocystis spp. in livestock animals: An emerging zoonosis from Sulaymaniyah Province - Abdullah, Shadan Hassan (Sulaimani Journal for Pure and Applied Sciences, 2023)
Blastocystosis is an infection with zoonotic parasite Blastocystis spp. commonly habitat the intestinal tract of wide range of hosts including human, animals and birds. The study conducted during June to November 2022 in Sulaymaniyah province for detection of Blastocystis spp. from livestock animals. For this purpose, a total of 250 fecal samples were collected randomly from cattle, sheep, and goats of different age groups. Based on microscopic examination of the examined fecal smears the overall prevalence rate of Blastocystis spp. was 24.4% among examined ruminant hosts. Higher prevalence rate has been reported from cattle 29% followed by sheep 27%, and goats 16%, with no significant differences. The study data confirmed Blastocystis colonization of livestock animals in the study area, further study for detection of various subtypes by applying of molecular techniques is essential to find out the infected subtypes and define their impact on public health.
Keywords: Blastocystis; ruminants; zoonotic; microscopy; Sulaymaniyah